2018
DOI: 10.1063/1.5019019
|View full text |Cite
|
Sign up to set email alerts
|

Electrical gain in interband cascade infrared photodetectors

Abstract: In order to achieve improved understanding and gain insights into the device operation of interband cascade infrared photodetectors (ICIPs) and ultimately to optimize the design, we present a comparative study of five long-wavelength (LW) ICIPs based on a type-II InAs/GaSb superlattice. This study shows how the device responsivity is affected by the individual absorber thicknesses and the number of cascade stages, through the impact of light attenuation. Additionally, this study further validates that the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The RTD quantum efficiency of η RTD = 0.15 is calculated for normal incidence considering an absorption coefficient of α = 1 × 10 4 cm −1 and only reflection at the air/semiconductor interface as loss factor . The amplification is therefore about double the gain observed in interband cascade photodetectors …”
Section: Resultsmentioning
confidence: 99%
“…The RTD quantum efficiency of η RTD = 0.15 is calculated for normal incidence considering an absorption coefficient of α = 1 × 10 4 cm −1 and only reflection at the air/semiconductor interface as loss factor . The amplification is therefore about double the gain observed in interband cascade photodetectors …”
Section: Resultsmentioning
confidence: 99%
“…Currently, IB QCIPs has two types of configuration: current-matched (designed to have an equal photocurrent in every single stage) and non-current-matched [39]. Hinkey and Yang described the IB QCIP structure with equal absorbers offering the potential for significant responsivity improvement assuming αL ≤ 0.2 (αL-Product of the absorption coefficient and the diffusion length) [40].…”
Section: Interband Quantum Cascade Infrared Photodetectors (Ib Qcips)mentioning
confidence: 99%
“…Currently, quantum well infrared photodetectors (QWIPs) and quantum cascade photodetectors (QCDs) for high speed MWIR applications have been demonstrated [7][8][9] . Nevertheless performance of QCDs is mainly limited by absorption efficiency and noise due to a short carrier lifetime 10-15 , and QWIPs have shortcomings in large dark currents and no response to normal incident light 7,16 .Compared with conventional photodetectors, interband cascade infrared photodetectors (ICIPs) have more flexibility to alleviate the limitation on absorber thickness due to a finite diffusion length so that all photo-generated carriers can be efficiently collected, while absorption of incident light can be ensured with multiple absorbers located in each stage connected in series 16 . On the other hand, the individual absorber thickness in every stage can be shortened to reduce the carrier transit time across a single stage.…”
mentioning
confidence: 99%
“…Another advantage of ICIPs is that noise is suppressed by the multiple discrete short absorbers, instead of a single long absorber 17,18 . As one of the most widely studied material system for MWIR, ICIPs based on InAs/GaSb type-II superlattice (T2SL) could offer several advantages such as wavelength tunability between 1 to 25 μm, excellent carrier transport properties and signal to noise ratio (SNR) 16 . Lotfi et al reported a three-stage ICIP based on InAs/GaSb/AlSb/InSb T2SLs with a cutoff wavelength around 4.2µm at 300K, and the corresponding 3-dB bandwidth was ~1.3 GHz under zero bias 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation